BrainDen.com - Brain Teasers
• 0 ## Question How old am I and how old are you, if I am twice the age you were, when I was your age.

Kowing that when you become my age, adding it to the age I will be then,

will add 72? Here's another way to put it.

I am twice the age you were when I was your age.

When you become my age, add it to the age I will be then, will add 72

How old am I and how old are you now?

Edited by aliz8

## Recommended Posts

• 0 How old am I and how old are you, if I am twice the age you were, when I was your age.

Kowing that when you become my age, adding it to the age I will be then,

will add 72? Here's another way to put it.

I am twice the age you were when I was your age.

When you become my age, add it to the age I will be then, will add 72

How old am I and how old are you now?

I believe the first part translates to: M=2*(U-(M-U)) --- or 3M = 4U, where M is "my age" and U is "your age". However, the wording for the second part is confusing. If interpreted as M+(M-U) = 72 --- or 2M-U = 72 then M = 57.6 and U = 43.2. However, I doubt that I understood the second part, as I would expect these to probably be integers.

##### Share on other sites

• 0 How old am I and how old are you, if I am twice the age you were, when I was your age.

Kowing that when you become my age, adding it to the age I will be then,

will add 72? Here's another way to put it.

I am twice the age you were when I was your age.

When you become my age, add it to the age I will be then, will add 72

How old am I and how old are you now?

24 & 48

##### Share on other sites

• 0 24 & 48

When I was 24, you would have been 0, and I would now be 2*0, or 0.

Edited by ogden_tbsa
##### Share on other sites

• 0 24 and 16

Edited by Mr. Wiggin
##### Share on other sites

• 0 Let x = younger age, y = older age and z = the difference between your age and mine. (I know z is non necessary but it actually makes the system easier to understand.)

Now, y-x = z

2x-2z = y-z

and x+y+2z = 72

x=18, y=24 and z=6

Here's some more explanation for my answer. You can set up three simulanious equations.

##### Share on other sites

• 0 Let x = younger age, y = older age and z = the difference between your age and mine. (I know z is non necessary but it actually makes the system easier to understand.)

Now, y-x = z

2x-2z = y-z

and x+y+2z = 72

x=18, y=24 and z=6

Here's some more explanation for my answer. You can set up three simulanious equations.

Close but no cigar

If I am 24 and you are 18, when you are 24 I will be 30 which only adds up to 54

M1 = my age now

M0 = my age when you were Y0 = Y1

M1 = M0 + x

Y1 = Y0 + x

Solving in terms of x yields:

Y0 = 2x

Y1 = M0 = 3x

M1 = 4x

Y2 = M1 (your age when you become my age now)

Y2 = Y1 + z = 3x + z

4x = 3x + z

z = x

M2 = 4x + x = 5x

Y2 = 3x + x = 4x

M2 + Y2 = 72

5x + 4x = 72

x = 8

Y1 = 24, M1 = 32

Thus, right now, I am 32 and you are 24. When I was your age (24) you were 16 which is half of 32. When you are 32, I will be 40 which adds to 72.

##### Share on other sites

• 0 The ages are 14 and 28 today. In 14 more years, when you're 28, I'll be 44. Which add to 72.

Solution in the Spolier

##### Share on other sites

• 0 The ages are 14 and 28 today. In 14 more years, when you're 28, I'll be 44. Which add to 72.

Solution in the Spolier

alright...my question is how are you going to age 16 years in only 14...is it space travel? it's space travel isn't it...

(28 + 14 = 42, not 44)

##### Share on other sites

• 0 "I am twice the age you were, when I was your age"

m = 2*(y-(m-y))

"When you become my age, add it to the age I will be then, will add 72"

y+(m-y) + m+(m-y) = 72

If you enter the following line at http://www.wolframalpha.com/

m=2*(y-(m-y)),m+(m+(m-y))=72,m,y

it will solve it for you without any more effort

the result:

m = 32, y = 24

##### Share on other sites

• 0 Ahhh... I'm a math teacher and I failed to execute the most important problem-solving step of all- "check your work!" I wrote the equations but didn't even solve them. LOL! I found two numbers that satisfied the first part so I just assumed that would be the solution. I fail!

##### Share on other sites

• 0 if x is my age and y is your age, then from the first line you get this:

x = 2(y-9x-y))

which simplifies to:

3x = 4y

the second statement gives you this:

y+(x-y) + (x+(x-y)) = 72

which simplifies to:

3x-y=72

then subsitute 4y for 3x, which gives 4y-y = 72,

which gives y=24

plug that back in, say 3x-24 = 72, and you get x=32

so, I am 32 and you are 24

##### Share on other sites

• 0 I believe the first part translates to: M=2*(U-(M-U)) --- or 3M = 4U, where M is "my age" and U is "your age". However, the wording for the second part is confusing. If interpreted as M+(M-U) = 72 --- or 2M-U = 72 then M = 57.6 and U = 43.2. However, I doubt that I understood the second part, as I would expect these to probably be integers.

The second wording is the same except How old am I and how old are you is placed last, and the word knowing was removed.

##### Share on other sites

• 0 24 & 48

Numbers do not add up right. They do add up 72 now.

Statement reads " If I am twice the age you were WHEN I WAS YOUR AGEAlso "When you reach my age".

How old am I NOW Your numbers just add 72, but everything else nothing.

##### Share on other sites

• 0 Close but no cigar

If I am 24 and you are 18, when you are 24 I will be 30 which only adds up to 54

M1 = my age now

M0 = my age when you were Y0 = Y1

M1 = M0 + x

Y1 = Y0 + x

Solving in terms of x yields:

Y0 = 2x

Y1 = M0 = 3x

M1 = 4x

Y2 = M1 (your age when you become my age now)

Y2 = Y1 + z = 3x + z

4x = 3x + z

z = x

M2 = 4x + x = 5x

Y2 = 3x + x = 4x

M2 + Y2 = 72

5x + 4x = 72

x = 8

Y1 = 24, M1 = 32

Thus, right now, I am 32 and you are 24. When I was your age (24) you were 16 which is half of 32. When you are 32, I will be 40 which adds to 72.

You got it. Very good. Stay tuned for a harder one in the future. Right now I have to run.

##### Share on other sites

• 0 if x is my age and y is your age, then from the first line you get this:

x = 2(y-9x-y))

which simplifies to:

3x = 4y

the second statement gives you this:

y+(x-y) + (x+(x-y)) = 72

which simplifies to:

3x-y=72

then subsitute 4y for 3x, which gives 4y-y = 72,

which gives y=24

plug that back in, say 3x-24 = 72, and you get x=32

so, I am 32 and you are 24

You are correct. Stay tuned for a harder one later.
##### Share on other sites

• 0 You got it. Very good. Stay tuned for a harder one in the future. Right now I have to run.

Don't run too far aliz8. You are beginning to write interesting posts which, while not stunningly difficult, may begin to be fun.

## Join the conversation

You can post now and register later. If you have an account, sign in now to post with your account. ×   Pasted as rich text.   Paste as plain text instead

Only 75 emoji are allowed.

×   Your previous content has been restored.   Clear editor

×   You cannot paste images directly. Upload or insert images from URL.